Bovine colostrum supplementation in prevention of upper respiratory tract infections – Systematic review, meta-analysis and meta-regression of randomized controlled trials - Maciej Hałasa; Magdalena Baśkiewicz-Hałasa; Dominika Jamioł-Milc; Dominika Maciejewska-Markiewicz; Karolina Skonieczna-Żydecka (Journal of Functional Foods, 2022)
Prevention from the upper respiratory tract infections (URTIs) is one of the best known of the numerous health benefits of bovine colostrum supplementation (BCS). We aimed to systematically review the effectiveness of colostrum supplementation to counteract URTIs. We systematically searched available databases and performed random-effect meta-analyses of the incidence of self-reported URTIs, their duration and severity. For the risk ratio (RR) of URTIs, our systematic review involved 445 randomized participants in 7 trials and was significantly diminished upon BCS (RR = 0.64 with a 95 % confidence interval of 0.498–0.822; z =  − 3.493, p < 0.001). This effect was found to be somewhat dependent on the supplementation duration (coefficient = 0.015, standard error = 0.008, Z = 1.89, p = 0.056). Our systemic review and meta-analysis including more than triple number of participants as compared to previous analysis of this kind, strongly confirms that BCS significantly reduces the incidence of URTIs. We also demonstrated that the efficacy of BCS can depend to some extend on the duration of supplementation, but neither on the dose size, sex distribution nor physical activity lifestyle.